2010
DOI: 10.1007/s13238-010-0038-6
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the α2A domain of integrin with small collagen fragments

Abstract: We here present a detailed study of the ligand-receptor interactions between single and triple-helical strands of collagen and the α2A domain of integrin (α2A), providing valuable new insights into the mechanisms and dynamics of collagen-integrin binding at a sub-molecular level. The occurrence of single and triple-helical strands of the collagen fragments was scrutinized with atom force microscopy (AFM) techniques. Strong interactions of the triple-stranded fragments comparable to those of collagen can only b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 53 publications
(67 reference statements)
3
57
0
1
Order By: Relevance
“…Our mass spectrometric analysis as well as NMR experiments enabled us to show for the first time the different characteristic composition and structural organization of the investigated bovine collagen hydrolysates induced by various hydrolysis techniques [14], [15], [37]. Furthermore, we report for the first time about the different biological activities of collagen hydrolysates on human articular chondrocytes, which might be due to different active ingredient(s) of various collagen hydrolysate preparations, as shown by our biophysical analysis.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Our mass spectrometric analysis as well as NMR experiments enabled us to show for the first time the different characteristic composition and structural organization of the investigated bovine collagen hydrolysates induced by various hydrolysis techniques [14], [15], [37]. Furthermore, we report for the first time about the different biological activities of collagen hydrolysates on human articular chondrocytes, which might be due to different active ingredient(s) of various collagen hydrolysate preparations, as shown by our biophysical analysis.…”
Section: Discussionmentioning
confidence: 69%
“…Collagen hydrolysates were dissolved in pure water at a concentration of 10 ng/mL, adsorbed onto mica discs (Plano, Germany), incubated for 15 min at room temperature, dried with nitrogen, and imaged under air in tapping mode with OMCL-AC240TS-W2 cantilevers (Atomic force). The data were processed using the MFP-3D interface built on IGOR PRO version 6.02A [14], [15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be demonstrated that different collagen hydrolysates differ in their physico-chemical properties, which could have an impact on the interaction of the peptides with certain integrin receptors (Siebert et al 2010;Stötzel et al 2012). Molecular weight distribution of the collagen peptides and the specific amino acid sequences might be of importance for the efficacy play a major role, whereas the Note: Data are presented as mean VAS Scores ± SEM at baseline (t 0 ) and after 12 weeks (t 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, at concentrations that were higher than 1 mg mL −1 , the sulfated polysaccharides exhibited inhibitory effects on neurite outgrowth. Therefore, the sulfated polysaccharides from mixtures of brown and green algae, with or without bioactive collagen fragments, can also be applied in addition to polySia or polySia mimicking molecules when lesions in neuronal tissues need to be cured …”
Section: Resultsmentioning
confidence: 99%